Numerical Investigation on the Creep Response of Concrete Structures by Means of a Multi-Scale Strategy - Saavedra-Flores, E; Pina, J; Godoy-Dellepiani, M (Elsevier Ltd, 2020)
In this paper, a multi-scale modelling strategy is proposed to investigate the creep behaviour of reinforced concrete structures. A Mean Field homogenisation procedure is adopted to compute the overall response of a high-strength concrete made of limestone inclusions embedded in a cement paste matrix. Finite element models of beams subjected to sustained bending loads are fully coupled to the time-dependant effective material law delivered by the homogenisation method. Furthermore, a Genetic Algorithm is used to improve the accuracy of the finite element predictions. The influence of relevant structural parameters, such as beam height, steel reinforcement ratio in tension and compression, and cement volume fraction, is assessed on the long term creep deflection over a period of five years. The long term multiplier factor, λΔ, defined as the creep deflection over the immediate deflection, is calculated numerically and discussed in detail. The above results provide further insight into the time-dependent deformation mechanisms present in concrete structures which are still not well-understood, and may shed more light on the improvement of current design equations and the development of complementary design guidelines. © 2020 Elsevier Ltd